2023
DOI: 10.1002/tox.23670
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA circSTIL inhibits ferroptosis in colorectal cancer via miR‐431/SLC7A11 axis

Abstract: Ferroptosis is an emerging programmed cell death and plays essential roles in tumorigenesis, including colorectal cancer (CRC). The present study intended to disclose the role of a novel oncogene circular RNA (circRNA) circSTIL in CRC phenotypes, especially ferroptosis. The expression of circSTIL was measured in CRC tissues and cells.Then, the impacts of circSTIL expression on the proliferation and ferroptosis of CRC cells were examined by loss-of-function assays in vitro. Bioinformatics, luciferase reporter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“… Ovarian cancer [ 144 ] CircSTIL/miR-431/SLC7A11 Negative CircSTIL sponges miR-431, leading to SLC7A11 upregulation. Colorectal cancer [ 145 ] Circ_0067934/miR-545-3p/SLC7A11 Negative Circ_0067934 sponges miR-545-3p, leading to SLC7A11 upregulation. Thyroid cancer [ 146 ] CircEPSTI1/miR-375_miR409-3P_miR-515-5p/SLC7A11 Negative CircEPSTI1 sponges miR-375, miR409-3P, and miR-515-5p, leading to SLC7A11 upregulation.…”
Section: Ferroptosis-regulating Cerna Networkmentioning
confidence: 99%
See 1 more Smart Citation
“… Ovarian cancer [ 144 ] CircSTIL/miR-431/SLC7A11 Negative CircSTIL sponges miR-431, leading to SLC7A11 upregulation. Colorectal cancer [ 145 ] Circ_0067934/miR-545-3p/SLC7A11 Negative Circ_0067934 sponges miR-545-3p, leading to SLC7A11 upregulation. Thyroid cancer [ 146 ] CircEPSTI1/miR-375_miR409-3P_miR-515-5p/SLC7A11 Negative CircEPSTI1 sponges miR-375, miR409-3P, and miR-515-5p, leading to SLC7A11 upregulation.…”
Section: Ferroptosis-regulating Cerna Networkmentioning
confidence: 99%
“…As an upregulated circRNA in chemoresistant ovarian cancer tissues compared to sensitive ones, circSnx12 knockdown enhances the chemosensitivity and increases apoptosis and ferroptosis of cisplatin chemoresistant ovarian cancer cells circSnx12/miR-194-5p/SLC7A11 axis [ 144 ]. CircSTIL is an increased circRNA in colorectal cancer, and its knockdown is associated with decreased proliferation and enhanced ferroptosis of colorectal cancer cells via the circSTIL/miR-431/SLC7A11 axis [ 145 ]. In thyroid cancer, circ_0067934 knockdown decreases proliferation and increases apoptosis and ferroptosis of malignant cells via the circ_0067934/miR-545-3p/SLC7A11 axis [ 146 ].…”
Section: Ferroptosis-regulating Cerna Networkmentioning
confidence: 99%
“…Knockdown of circSTIL induces cellular Fe2+ and lipid ROS accumulation, activates cellular ferroptosis, and inhibits colorectal cancer cell proliferation. In addition, circSTIL targets SLC7A11 by competitively binding to miR-431 to regulate ferroptosis, providing a new target for the treatment of colorectal cancer ( Li et al, 2023 ).…”
Section: Ferroptosis Related Circrna Involvement In Regulating Cancer...mentioning
confidence: 99%
“…Recent evidence demonstrates that circRNAs have multiple biological functions, including cis‐acting regulation of host gene expression, regulation of miRNA target genes by acting as miRNA sponges, protein translation, and protein interaction 14 . CircRNAs have been implicated in a variety of pathological and physiological processes, including various types of malignant cancer, cardiovascular disease, and endocrine dysfunctions 13,15–17 . Recent research has demonstrated that circRNA is essential for developing endometrial receptivity and embryo implantation.…”
Section: Introductionmentioning
confidence: 99%
“…14 CircRNAs have been implicated in a variety of pathological and physiological processes, including various types of malignant cancer, cardiovascular disease, and endocrine dysfunctions. 13,[15][16][17] Recent research has demonstrated that circRNA is essential for developing endometrial receptivity and embryo implantation. Song et al discovered that several circRNAs were differentially expressed in the endometrium of dairy goats and suggested that circRNAs may be potential regulators of receptive endometrium.…”
mentioning
confidence: 99%